2009
DOI: 10.1002/pssr.200903155
|View full text |Cite
|
Sign up to set email alerts
|

Rectifying properties and photoresponse of CVD diamond p(i)n‐junctions

Abstract: The current-voltage characteristics and photoresponse of mesa structured {111}-oriented homoepitaxial CVD diamond pin-junctions with different intrinsic layer thickness are investigated. When a sufficient thick intrinsic layer is present, a rectification ratio of 10 8 at ± 10 V could be obtained. Good rectifying diodes show a high photoresponse ratio between 210 nm (above bandgap) and 500 nm (below bandgap), making them suitable for UV detection purposes. The results are compared with similar measurements carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Diamond is a unique material well known for its outstanding properties which make it the material of choice for high‐end applications such as cutting of hard materials, radiation detection, electroanalysis, bio‐sensing, high‐power high‐frequency switching, and quantum computing 1–6. For many of these applications the semiconducting properties of diamond are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond is a unique material well known for its outstanding properties which make it the material of choice for high‐end applications such as cutting of hard materials, radiation detection, electroanalysis, bio‐sensing, high‐power high‐frequency switching, and quantum computing 1–6. For many of these applications the semiconducting properties of diamond are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…The rectification ratios of the diode samples fabricated in this study at AE10 V at room temperature were found to be between 4:4 Â 10 3 -5:2 Â 10 6 . Although, rectification ratios as high as $10 8 {10 10 have recently been reported in diamond devices at comparable bias voltages, 31,32) those results were obtained from doped and highly doped diamond devices. In contrast, the rectification ratio of 10 6 observed here is comparable to the best results previously reported by others on intrinsic films.…”
Section: Fabrication Of the Mcd/ncd Devices And Their Current-voltage...mentioning
confidence: 87%
“…In addition, due to the large exciton binding energy (80 meV), a diamond diode can realize high-intensity, free-exciton emission (wavelength of about 235 nm) at room temperature, which has a greater potential in the deep ultraviolet and the extreme UV deep-ultraviolet detectors [ 5 ]. Compared with the unipolar Schottky barrier diodes (SBDs) [ 6 ], the bipolar p-n diodes (PNDs) are attractive due to their capability of handling higher currents and high voltages at the same time [ 7 , 8 , 9 , 10 , 11 ]. In addition, they present lower on-resistance ( R on ) and less static power loss in high-voltage applications thanks to the conductivity modulation effect [ 12 ].…”
Section: Introductionmentioning
confidence: 99%